Determinant Factors of Adoption of Introduced Soil Conservation Structures in North Gondar Zone, Ethiopia (International Journal of Scientific Research and Management (IJSRM), 2018)
Soil erosion is a very severe problem in the highlands of Ethiopia, especially in Northern and central highlands of Ethiopia. In the country, efforts to conserve soil resources and prevent degradation dated back to the mid-1970s and 80s. However, the efforts put towards the promotion of the technologies, so far seem to have had limited impact in increasing the sustained use of conservation measures in different parts of the country, including Sabiya Sayna Kebele. The main purpose of this study was, therefore, to assess the sustainable use of physical conservation measures introduced through a major soil conservation.. Specifically, the study was conducted to assess farmers’ perception towards the major introduced conservation structures; identify factors determining the adoption of these structures; and assess existing constraints to and options for sustained use of conservation structures in the study area. The study selected purposively of two sub-Kebeles where the recent intervention has already been implemented, and a total of 130 households were randomly selected from the sub-watersheds using the proportions-to-size technique of sample allocation. The study recommends that adequate consideration of the significant influential factors should be taken so as to better promote the sustainable use and widespread adoption of introduced conservation structures.